Study on the Carcass Traits, Meat Quality, and Nutritional Attributes of Six Kinds of Jiangxi Local Breeds Cattle - Yang Zhang; Yuting Wei; Guwei Lu; Youxiang Yang; Yuting Pan; Chuanpei Fu; Fazhan Tian; Qinghua Qiu; Xianghui Zhao; Yanjiao Li; Lingli Chen; Wenjun Wang; et al. (Animals, 2024)
The purpose of this study is to explore the carcass traits, meat quality, and nutritional attributes of local yellow cattle (Guangfeng, Ji’an, and Jinjiang) and buffalo (Poyanghu, Xiajiang, and Xinfeng mountain) in Jiangxi Province, and compare the differences among different breeds. The results showed that the dressing percentage, net meat percentage, and meat–bone ratio of Jinjiang cattle were highest, and that Jinjiang cattle had the best meat production performance. Regarding meat quality, the pH24h value of all breeds was at normal level, and no dark-cutting beef was produced. Poyanghu buffalo and Xinfeng mountain buffalo had higher redness (a*) values, and Guangfeng cattle had the best water retention and tenderness. The intermuscular fat of yellow cattle breeds was higher than that of buffalo breeds; Poyanghu buffalo had the highest crude protein content. The composition of amino acids and fatty acids was different among breeds, and the composition of Jiangxi breeds was healthy. The muscle fibers of buffalo breeds are generally smaller and denser than those of yellow cattle breeds. The MyHC-Ⅰ, MyHC-Ⅱa, and MyHC-Ⅱx were the main types of muscle fibers of Jiangxi local breeds, and the proportion varied with different breeds. This work elucidated the carcass characteristics, meat quality, and nutritional attributes of Jiangxi breed cattle to provide a theoretical basis for optimizing the development of beef cattle industry.